Assessment of cytological features of glandular lesions of the cervix on conventional smear preparations—a comprehensive study from a tertiary care hospital. Issue 3 (19th November 2020) - Mantri, Shweta; Ravikumar, Gayatri; Crasta, Julian
Abstract: Background: Atypical glandular cells (AGC) as a diagnostic category in cervicovaginal cytology remains as a challenge to cytopathologists. Aims: The aim of the present study is to identify the cytological features helpful in categorizing AGC as reactive or neoplastic upon correlation with histology. Materials and Methods: The study was a retrospective review of cervical smears, with histopathological follow up, reported as glandular lesions for a period of 9 years. The architectural and nuclear features studied were adapted from The Bethesda System (TBS) to stratify the lesions as AGC, AGC‐FN (atypical glandular cells favour neoplasia) and adenocarcinoma. The cytological categories were correlated with histology. Results: A total of 89 cases of which 67 (AGC NOS = 34, AGC FN = 19, adenocarcinoma = 14) with histology were reviewed. Neoplastic lesions were encountered in 14 cases (34.6%). Of the cases diagnosed as AGC‐NOS, AGC‐FN and adenocarcinoma, 26.5%, 68.4% and 100% respectively were neoplastic on histopathology. Squamous lesions accounted for 14.9% of all the glandular lesions. Rosette or acinar formation and loss of polarity frequently observed in neoplastic lesions as compared to reactive changes (p = 0.0004, p = 0.001). Of the nuclear features, nuclear hyperchromasia or coarse clumping of chromatin along with nuclear membrane irregularity and nuclear pleomorphism was frequently associated with neoplastic lesions as compared to reactive conditions (p = 0.007, p = 0.001, p = 0.0002). Conclusion: A diagnosis of AGC at cytology harbors significant number of malignant lesions when confirmed on biopsy. Architectural features complemented with nuclear characteristics helps in differentiating between reactive and neoplastic conditions. Hence stratifying glandular lesions at cytology according to TBS helps in the management.